Ultrasonographic Detection of Joint Abnormalities in Rheumatoid Arthritis: A Cross-sectional Study - Alka Agrawal; Prachi Shukla; Hema Dhakad; Mona; Mayank Patidar; Manzill (APIK Journal of Internal Medicine, 2025)
Background: Rheumatoid arthritis (RA) is an autoimmune disorder affecting the joints, causing inflammation and potential structural damage. While conventional radiography often reveals damage only in later stages, ultrasonography (USG) offers a dynamic, noninvasive imaging option with greater patient acceptability. Materials and Methods: A cross-sectional study was conducted at a medical college hospital in India, involving 50 clinically diagnosed RA patients. US (7–13 MHz) was used to assess wrist and hand joints for synovial hypertrophy, vascularity using power Doppler (PD), bone erosions, and joint effusion. Results: Among patients aged 20–80 years, the mean age was 54 years, the median age was 49.5 years with an interquartile range of 11.5 years, and 84% were female. US detected synovial thickening in 80% of wrist joints and 68% of hand joints, with bone erosions found in 42% of wrist and 36% of hand joints. PD detected increased vascularity in 60% of cases. X-rays revealed soft-tissue swelling in 16% of wrist and 8% of hand joints, with bone erosions in 24% of wrist joints. US showed higher sensitivity (83.3% for wrist and 87.5% for hand) and specificity (68.4% for wrist and 71.4% for hand) in detecting bone erosions compared to X-ray. Conclusion: Grayscale USG and PD are valuable tools for assessing joint abnormalities in patients with RA. Their ability to detect synovial changes and vascular activity supports accurate disease evaluation and aids in treatment planning, particularly in hand and wrist joints.